Polymorphonuclear myeloid‐derived suppressor cells link inflammation and damage response after trauma. Issue 6 (12th October 2021) - Li, Xinyao; Liu, Jingping; Xing, Zhe; Tang, Jian; Sun, Hengbiao; Zhang, Xiaogang; Lv, Shuaijun; Chen, Ziyang; Shi, Mengyu; Chen, Meiqi; Zuo, Shaowen; Lyu, Xiaoming; et al.
Abstract: Elimination of the posttraumatic inflammatory response and recovery of homeostasis are crucial for the positive prognosis of trauma patients. Myeloid‐derived suppressor cells (MDSCs) are known to play a regulatory role in the posttraumatic immune response in mice, but their induction source and involved potential mechanism are poorly understood. Here, we report that polymorphonuclear MDSCs (PMN‐MDSCs) are activated after trauma and are closely associated with the progression of the posttraumatic inflammatory response. In humans, lectin‐type oxidized LDL receptor 1 (LOX1) was used to specifically characterize LOX1 + PMN‐MDSCs. Trauma patients showed high intracellular reactive oxygen species (ROS) production, as well as activation of LOX1 + PMN‐MDSCs. These MDSCs contribute to the anti‐inflammatory immune response by regulating the Treg/Th17 and Th2/Th1 balances after trauma, increasing the levels of anti‐inflammatory factors, and decreasing the levels of proinflammatory factors. The number of LOX1 + PMN‐MDSCs was positively correlated with the positive clinical prognosis of trauma patients with infection. Activation of LOX1 + PMN‐MDSCs is mediated by NF‐κB signal, and TGF‐β1 may be as an important inducer for LOX1 + PMN‐MDSCs in the posttraumatic cytokine environment. In a pseudofracture trauma mouse model, we also observed the activation of PMN‐MDSCs, accompanying high levels of intracellular ROS production, NF‐κB phosphorylation, and changes in the inflammatory environment, in particularly by regulating the Treg/Th17 and Th2/Th1 balance. And more significantly, posttraumatic inflammation was alleviated in mice after transferring trauma‐derived PMN‐MDSCs, but aggravated after injecting with Gr1 agonistic antibody. These findings provide evidence for the specific role of PMN‐MDSCs in the regulation of posttraumatic inflammation. Graphical Abstract: Role of PMN‐MDSCs in the anti‐inflammatory immune response by regulation of the Treg/Th17 and Th2/Th1 balances after trauma.